Analysis of Electrical Energy Consumption and Savings Potential at PT. Sawitech Manufacturing Workshop Through Energy Audit Method - Erik Ardinata; Dori Yuvenda; Arwizet K; Andre Kurniawan (Unversitas Negeri Padang, 2026)
This study aims to analyze the electrical energy consumption profile at PT. Sawitech manufacturing workshop and office areas, identify equipment contributing most to total energy use, and calculate savings potential through energy audit method. The research used descriptive quantitative approach by directly measuring electrical load, observing equipment operation hours, and applying load factor values. Total annual energy consumption based on manual calculation was 68,745.63 kWh/year, while RETScreen Expert simulation yielded 71,673 kWh/year (4.08% difference). Energy Consumption Intensity (ECI) based on total area of 2,272 m2 was 30.25 kWh/m2/year, classified as Very Efficient according to SNI 6196:2011 and ESDM Ministerial Regulation No. 13/2012. The highest energy consumers were welding transformer (22,680 kWh/year), compressor (17,280 kWh/year), and large blower (1,999.2 kWh/year). Energy savings recommendations include replacing conventional welding transformer with inverter based unit, substituting large blowers with more efficient axial fans, upgrading lighting to LED, and replacing conventional AC with inverter AC. Implementation of these recommendations can reduce energy consumption by 8,518.6 kWh/year (11.8%) and save costs of Rp 9,013,754/year. Carbon emissions before savings measures amounted to 59.81 ton CO 2/year, decreasing to 52.40 ton CO 2/year after implementation, a reduction of 7.41 ton CO 2/year (12.39%). Payback period of total investment (Rp 105,130,400) is approximately 6.9 years